An appraisal of methods used in the examination of retail samples of cows milk. - Greenwood, M. H. (Cambridge University Press, 1988)
The use of the methylene blue test for the examination of cows milk was investigated in an inter-laboratory survey. A poor relationship was found between results of these tests and total viable counts. Coliforms were detected in a large number of pasteurized milks, indicating frequent post-pasteurization contamination. No relationship was found between the results of the methylene blue test and the presence of coliforms. Results from this survey highlight the need for reappraisal of the methylene blue test as a statutory method for the examination of milk. A total viable count and coliform test are suggested for providing information regarding dairy hygiene and the quality of the product at the point of retail sale.